Party Facts: A database of political parties worldwide - Holger Döring; Sven Regel (Party Politics, 2019)
Here, we present Party Facts (www.partyfacts.org), a modern online database of political parties worldwide. With this project, we provide a comprehensive database of political parties across time and world regions, link party information from some of the core social science data sets, and offer a platform to link political parties across data sets. An initial list of 4000 core parties in 212 countries is mainly based on four major data sets. The core parties in Party Facts are linked with party information from some of the key social science data sets, currently 26. From these data sets, we have included and linked about 15,000 party observations. Party Facts is an important step in developing a more coherent operationalization of political parties across time and space and a gateway to existing data sets on political parties. It allows answering innovative party research questions that require the combination of multiple data sets.
Keywords: 330; collaborative data collection; data sets; political parties